Piplartine suppresses proliferation and invasion of hepatocellular carcinoma by LINC01391-modulated Wnt/β-catenin pathway inactivation through ICAT. (28th September 2019) - Fan, Xiaoxi; Song, Jingjing; Zhao, Zhongwei; Chen, Minjiang; Tu, Jianfei; Lu, Chenying; Wu, Fazong; Zhang, Dengke; Weng, Qiaoyou; Zheng, Liyun; Xu, Min; Ji, Jiansong
Abstract: Although piplartine is regarded as an anticancer agent, the relationship between long noncoding RNAs (lncRNAs), which are involved in various diseases (e.g., tumors) and piplartine in hepatocellular carcinoma (HCC) remains unclear. We identified LINC01391 using microarray analysis and validated its expression by qRT-PCR. Functional assays were applied to evaluate the biological effects of LINC01391 and inhibitory of β-catenin and T-cell factor (ICAT) on HepG2 and SMMC-7721 cells. The binding relationship between LINC01391 and ICAT was determined by RNA pull-down and RNA immunoprecipitation (RIP). Results showed that piplartine attenuated cell proliferation and invasion but promoted cell apoptosis. Upregulation of LINC01391 induced by piplartine inhibited HCC cell proliferation, invasion in vitro, and tumor growth in vivo. LINC01391 interacted with ICAT and promoted its inhibitory effect on the Wnt/β-catenin pathway, as enhanced interaction between β-catenin and ICAT, and dampened interaction of β-catenin and TCF/LEF were induced by overexpression of LINC01391. Knockdown of ICAT also promoted cell proliferation in vitro and tumor growth in vivo. Our study supported a role for piplartine and LINC01391 in HCC treatment. We found that LINC01391 inhibited the Wnt/β-catenin pathway and suppressed tumor growth via ICAT. Highlights: Piplartine attenuated cell proliferation and invasion but promoted cell apoptosis. Upregulation of LINC01391 induced by piplartine inhibited HCC cell function and tumor growth. LINC01391 interacted with ICAT and promoted its inhibitory effect on Wnt/β-catenin pathway. Knockdown of ICAT also promoted cell proliferation in vitro and tumor growth in vivo.